Characteristics of Asthma Patients Seeking Care at West Java’s Top Referral Hospital, Indonesia - Juan Achmad Yudistira; Emmy Hermiyanti Pranggono; Anna Tjandrawati; Primal Sudjana (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: The increasing incidence of asthma in many countries in recent decades makes asthma a global health problem. The aim of the study was to determine the characteristics of asthma patients at the Respirology Outpatient Clinic of Dr. Hasan Sadikin General Hospital as West Java’s Top referral hospital. Methods: The study used a cross-sectional design. The study population was the medical record data of asthma patients at the Respirology Outpatient Clinic during June 2012–June 2013. There were 1,591 patient’s medical records at the Respirology Outpatient Clinic of Dr. Hasan Sadikin General Hospital Bandung in that period and 140 medical records were diagnosed with asthma. Seventy medical records were excluded because of inadequate data and 70 medical records were the sample of this study. The collected data were presented using percentage. Results: Seventy percent of the cases were female. From these cases 34% of patients were aged 51–60 years. The partially controlled type was the most frequent type of asthma (62%). The most common sign and symptom was shortness of breath (86%). The most common drug used was Beta 2 agonist drugs (90%).Conclusions: The characteristic of asthma is that the patients are mostly female. Mostly the patients were in the age range of 51–60 years. The partially controlled type is the most frequent type of asthma. Shortness of breath is the most common clinical manifestation in asthma. Beta 2 agonist is the most used drug for asthma. [AMJ.2017;4(1):78–82]DOI: 10.15850/amj.v4n1.1025